2012
DOI: 10.1021/je2013878
|View full text |Cite
|
Sign up to set email alerts
|

Activity Coefficients at Infinite Dilution of Volatile Compounds in Water: Effect of Temperature and Salt Concentration

Abstract: Activity coefficients at infinite dilution in water have been determined for some aroma compounds detected in brown crab liquid effluent produced during boiling (1-octen-3-ol, 1-penten-3-ol, 3-methylbutanal, hexanal, benzaldehyde, 2,3-pentadione and ethyl acetate) by using the headspace gas chromatography technique (HSGC). Experimental data have been obtained over the temperature range of 40ºC to 50ºC. In this work, activity coefficients at infinite dilution for different type of systems have been considered: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…Table 5 lists the slopes of these plots together with the values previously reported in the study of the activity coefficients at infinite dilution. It can be observed that the values of the slopes obtained for the ln (J i, salty solutions /J i,non-saltysolution ) were lower than the values previously reported [7]. Therefore, blocking effect cannot be considered negligible.…”
Section: Effect Of the Salt Content In The Feed Solutioncontrasting
confidence: 57%
See 4 more Smart Citations
“…Table 5 lists the slopes of these plots together with the values previously reported in the study of the activity coefficients at infinite dilution. It can be observed that the values of the slopes obtained for the ln (J i, salty solutions /J i,non-saltysolution ) were lower than the values previously reported [7]. Therefore, blocking effect cannot be considered negligible.…”
Section: Effect Of the Salt Content In The Feed Solutioncontrasting
confidence: 57%
“…In Eq. 9 with data of the activity coefficients obtained in previous work [7]. Table 5 lists the slopes of these plots together with the values previously reported in the study of the activity coefficients at infinite dilution.…”
Section: Effect Of the Salt Content In The Feed Solutionmentioning
confidence: 63%
See 3 more Smart Citations